2021
DOI: 10.47853/fas.2021.e27
|View full text |Cite
|
Sign up to set email alerts
|

A study on Kudoa septempunctata infection from sashimi and sushi of olive flounder Paralichthys olivaceus in Busan, South Korea

Abstract: Kudoa septempunctata has been reported as a new parasite in aquacultured olive flounder Paralichthys olivaceus, and also as a causative agent of food poisoning in humans. This paper investigated the infection of K. septempunctata in 216 sashimi and 20 sushi made of olive flounders in Busan, Korea. Among 236 samples, K. septempunctata was detected in eleven sashimi with 6-7 polar capsules by the microscopy. Among eleven sashimi, five sashimi were positive in Polymerase Chain Reaction (PCR) assay with the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Whereas there are 2 alleles (rnl-1 and rnl-2) for rnl, which differ at 2 SNPs [11]. Studies have shown that K. septempunctata found in Japan mainly has the ST1 or ST2 genotype, whereas ST3 genotype is found in Korea [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas there are 2 alleles (rnl-1 and rnl-2) for rnl, which differ at 2 SNPs [11]. Studies have shown that K. septempunctata found in Japan mainly has the ST1 or ST2 genotype, whereas ST3 genotype is found in Korea [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%